Situation Report: Hungary, 11 April 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Ambassador to Prague Raises Question of Relations with West Germany The Rakosi Era Is Criticized Again New Labor Instructions The Mechanization of Agricultural Work New Members Asking for Admission to the Agricultural Cooperatives